2021
DOI: 10.3389/fendo.2021.717288
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Clinical Pregnancy Failure Prediction Model for Poor Ovarian Responders During IVF/ICSI

Abstract: BackgroundsDespite the great advances in assisted reproductive technology (ART), poor ovarian response (POR) is still one of the most challenging tasks in reproductive medicine. This predictive model we developed aims to predict the individual probability of clinical pregnancy failure for poor ovarian responders (PORs) under in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI).MethodsThe nomogram was developed in 281 patients with POR according to the Bologna criteria from January 2016 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Some clinical prediction models have been developed to estimate the chances of IVF success in different populations over the last three decades ( 16 , 17 ). In a clinical pregnancy failure prediction model based on 281 POR patients, is still conducted according to the Bologna criteria, cannot be distinguished the biological heterogeneity of patients with POR ( 18 , 19 ). Another study found independent predictors of live birth in POR patients based on the POSEIDON criteria, but failed to develop a complete live birth predictive model ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical prediction models have been developed to estimate the chances of IVF success in different populations over the last three decades ( 16 , 17 ). In a clinical pregnancy failure prediction model based on 281 POR patients, is still conducted according to the Bologna criteria, cannot be distinguished the biological heterogeneity of patients with POR ( 18 , 19 ). Another study found independent predictors of live birth in POR patients based on the POSEIDON criteria, but failed to develop a complete live birth predictive model ( 20 ).…”
Section: Discussionmentioning
confidence: 99%